Ultrafast Acoustofluidic Exfoliation of Stratified Crystals. Issue 20 (30th March 2018) - Ahmed, Heba; Rezk, Amgad R.; Carey, Benjamin J.; Wang, Yichao; Mohiuddin, Md; Berean, Kyle J.; Russo, Salvy P.; Kalantar‐zadeh, Kourosh; Yeo, Leslie Y.
Abstract: While the remarkable properties of 2D crystalline materials offer tremendous opportunities for their use in optics, electronics, energy systems, biotechnology, and catalysis, their practical implementation largely depends critically on the ability to exfoliate them from a 3D stratified bulk state. This goal nevertheless remains elusive, particularly in terms of a rapid processing method that facilitates high yield and dimension control. An ultrafast multiscale exfoliation method is reported which exploits the piezoelectricity of stratified materials that are noncentrosymmetric in nature to trigger electrically‐induced mechanical failure across weak grain boundaries associated with their crystal domain planes. In particular, it is demonstrated that microfluidic nebulization using high frequency acoustic waves exposes bulk 3D piezoelectric crystals such as molybdenum disulphide (MoS2 ) and tungsten disulphide (WS2 ) to a combination of extraordinarily large mechanical acceleration (≈10 8 m s −2 ) and electric field (≈10 7 V m −1 ). This results in the layered bulk material being rapidly cleaved into pristine quasi‐2D‐nanosheets that predominantly comprise single layers, thus constituting a rapid and high throughput chip‐scale method that opens new possibilities for scalable production and spray coating deposition. Abstract : The ability to rapidly exfoliate 3D bulk transition metal dichalcogenide crystals into quasi‐2D nanosheets is demonstrated using a novel acoustomicrofluidic nebulization technique that exploits the inherent piezoelectricity of the material together with the large mechanical acceleration and electric field associated with the high‐frequency sound wave excitation.